Fiscal Policy in Latin America Countercyclical and Sustainable at Last? - Daude, Christian (OECD Publishing, 2010)
This paper analyses fiscal policy for several economies in Latin America, from the early nineties to the 2009 crisis. We present original estimates of cyclically-adjusted public revenues for Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico, Peru and Uruguay implementing the standardised OECD methodology and extending it to include commodity cycles, which have a direct and significant effect on the fiscal balance of several Latin American countries. Based on these estimates, we evaluate the size of automatic tax stabilisers and the cyclicality of discretionary fiscal policy. Additionally, we highlight the uncertainty stemming from the estimation of the output gap, due to large and simultaneous cyclical, temporary and permanent shocks in several Latin American economies
Keywords: Development